(2+1)-dimensional dynamical black holes in Einstein-nonlinear Maxwell theory - Gurtug, O.; Mazharimousavi, S. Habib; Halilsoy, M. (World Scientific Publ Co Pte Ltd, 2018)
Radiative extensions of BTZ metric in 2 + 1 dimensions are found which are sourced by nonlinear Maxwell fields and a null current. This may be considered as generalization of the problem formulated long go by Vaidya and Bonnor. The mass and charge are functions of retarded/advanced null coordinate apt for decay/inflation. The new solutions are constructed through a Theorem that works remarkably well for any nonlinear electrodynamic model. Hawking temperature is analyzed for the case of the Born-Infeld electrodynamics.
Keywords: Radiating black hole; Einstein-Power-Maxwell field; Born-Infeld